DETERMINASI PENYERAPAN ANGGARAN BELANJA MODAL PERANGKAT DAERAH PROVINSI SUMATERA SELATAN - Kusnadi, Mutiara Dwi; Dewata, Evada; Satriawan, Indra (Jurnal Riset Terapan Akuntansi, 2025)
This study was designed to identify the extent of contribution made by budget planning, budget execution, and the government’s internal control system toward optimizing capital expenditure absorption within regional apparatus organizations in South Sumatra Province. The research was prompted by real-world observations that revealed disparities in budget absorption, which tends to be low in the early quarters and spikes significantly toward the end of the fiscal year. A quantitative approach was employed in this study, utilizing questionnaires distributed to 164 respondents from 41 regional government institutions. The empirical data analysis revealed that budget formulation, budget execution, and internal government oversight each contribute positively and significantly to capital expenditure absorption. Collectively, these three variables demonstrate a strong and coordinated influence in enhancing budget absorption. These findings suggest that a well structured planning framework, targeted execution, and consistent internal monitoring serve as strategic cornerstones in achieving optimal capital budget absorption performance. Keywords: Planning, implementation, SPIP, budget absorption